Photocatalytic study of TiO2 thin films modified with Anderson-type polyoxometalates (Cr, Co and Ni): Experimental and DFT study. (1st February 2023) - Diaz-Uribe, Carlos; Duran, Freider; Vallejo, William; Puello, Esneyder; Zarate, Ximena; Schott, Eduardo
Graphical abstract: Three Anderson-type polyoxomolybdates with general formula (NH4 )6-n [XMo6 O24 H6 ] −6+n where X=Co 3+, Cr 3+, and Ni 2+ were deposited on TiO2 thin films, and the methylene blue (MB) dye adsorption capacity and photocatalytic degradation were studied. Results showed that CrMo6 /TiO2 was the best photocatalyst in between the studied systems. Abstract: In this work, three Anderson-type polyoxomolybdates (POMs) with general formula (NH4 )6-n [ XMo 6 O 24 H 6 ] −6+ n where X = Co 3+, Cr 3+, and Ni 2+ were deposited on TiO2 thin films Furthermore, the methylene blue (MB) dye adsorption capacity and photocatalytic degradation were studied. Morphological results show that the POMs/TiO2 films have a more heterogeneous surface in terms of particle size and distribution than bare TiO2 films. Optical characterization indicated that the CrMo6 /TiO2 material had the lowest band gap energy with a value of 2.8 eV. The adsorption results show that the maximum percentage of MB adsorption was 37 % for NiMo6 /TiO2 while bare TiO2 has only 9.2 %. The MB adsorption on POMs-TiO2 was modeled using and the Freundlich model showed the best fit in all studied films for MB removal. The MB photodegradation values shows this tendency 12 % for bare TiO2, 55 % for NiMo6 /TiO2, 73 % for NiMo6 /TiO2 and, 83 % for CrMo6 /TiO2 . Finally, DFT calculations were performed to characterize the geometry and electronic structure of the all compounds studied in this work, with the aim to explain the observed experimental results.